UTILIZING LINGUISTIC LANDSCAPE IN ENGLISH AS A FOREIGN LANGUAGE LEARNING - Yendra, Yendra; Satria, Willy (TELL - US JOURNAL, 2024)
This study aims to explore the utilization of linguistic landscape (LL) in English as a Foreign Language (EFL) learning. This study adopts a qualitative descriptive  approach, also referred to as a theoretical review. This study examines various perspectives from relevant literature to gain deeper insights into the utilization of LL in educational contexts. The method employed involves a comparative analysis of previous LL research. The primary sources for this study include research reports, journal articles, books, and other scholarly works that explore LL as a linguistic, social, and educational phenomenon. The findings of this research highlight several key concepts and strategies that can be applied to enhance the use of LL in EFL learning. Furthermore, the results indicate that integrating LL into EFL instruction provides an authentic and contextual approach, enabling learners to develop various language skills, including: mastery of English vocabulary, comprehensive reading ability, awareness of multilingualism, understanding of social, cultural, and economic contexts, as well as the ability to conduct critical discourse analysis.